Modified manganese iron lithium phosphate cathode material, preparation method and application thereof
Patent Information
- Application Number
- CN202311710381.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-13
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-12-13
AI Technical Summary
目前磷酸锰铁锂主要通过固相法或液相法合成,固相法前驱体接触不充分,制备得到的粒子尺寸大、分布不均匀造成材料一致性较差;液相法包括水热法和共沉淀法,其中水热法对反应设备要求高,需在高温高压反应釜中操作,不易实现产业化,共沉淀法操作相对简单、容易实现量产
[0034]The method for preparing modified lithium manganese iron phosphate cathode material provided by this invention introduces a nickel source in the co-precipitation reaction to avoid excessive growth of some grains in the subsequent sintering process, thereby ensuring the high compaction density of the final product. Introducing a carbon source and adding a pulverization process between the two sintering processes can not only further control the particle size of the final product and facilitate the nano-sized grains, but also shorten the electron transport distance, thereby further improving the compaction density and conductivity. Applying this cathode material to batteries can improve the specific capacity and rate performance of the batteries.
Smart Images

Figure CN117923451B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery technology, specifically relating to a modified lithium manganese iron phosphate cathode material, its preparation method, and its application. Background Technology
[0002] Lithium manganese iron phosphate (LMP) is a novel cathode material obtained by adding manganese to lithium iron phosphate (LFP). Compared to LFP, it offers advantages such as higher safety, higher cycle stability, and a higher voltage platform. Currently, LMP is mainly synthesized through solid-phase or liquid-phase methods. Solid-phase methods suffer from insufficient precursor contact, resulting in large particle sizes and uneven distribution, leading to poor material consistency. Liquid-phase methods include hydrothermal and co-precipitation methods. The hydrothermal method requires sophisticated equipment, operating in a high-temperature, high-pressure reactor, making industrialization difficult. The co-precipitation method is relatively simpler and easier to mass-produce. However, the LMP particles obtained by these methods are large in size and have low compaction density, limiting the specific capacity of the LMP material. Furthermore, LMP itself has poor conductivity, affecting the rate discharge performance of the battery. Currently, most methods aim to improve the conductivity of LMP by coating it with a highly conductive carbon layer. However, the carbon coating still results in a large particle size, hindering the improvement of the compaction density and further limiting the specific capacity. Therefore, how to improve both the specific capacity and rate performance of lithium manganese iron phosphate cathode materials is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0003] This invention provides a method for preparing a modified lithium manganese iron phosphate cathode material. By introducing a nickel source and a carbon source and limiting the particle size of the pulverized product, it is beneficial to prevent excessive grain growth, improve conductivity and reduce particle size, ensure the high compaction density of the final product and shorten the electron transport distance. Applying this cathode material to batteries is beneficial to improving the specific capacity and rate performance of the batteries.
[0004] The present invention also provides a modified lithium manganese iron phosphate cathode material. Since it is prepared by the above method, when this cathode material is applied to a battery, the battery exhibits excellent performance in terms of specific capacity and rate performance.
[0005] The present invention also provides a positive electrode sheet, which, by comprising the above-mentioned positive electrode material, is assembled into a battery, and the battery exhibits excellent performance in terms of specific capacity and rate performance.
[0006] The present invention also provides a lithium-ion battery having a high specific capacity and excellent rate performance.
[0007] In a first aspect, the present invention provides a method for preparing a modified lithium manganese iron phosphate cathode material, comprising the following steps:
[0008] Manganese, iron, nickel, and phosphorus sources are mixed with water to obtain the first slurry;
[0009] The first slurry was treated under a nitrogen atmosphere at a rotation speed of 200-300 r / min and a temperature of 50-60°C for 10-22 h to obtain a precipitated product.
[0010] The precipitate was washed, filtered, and dried to obtain the first precursor.
[0011] The first precursor, lithium source, and carbon source are mixed and subjected to a first sintering treatment under an inert atmosphere to obtain a second precursor; the mass of the carbon source is 4 to 10% of the sum of the mass of the first precursor and the lithium source.
[0012] The second precursor is pulverized to obtain a pulverized product, and the particle size of the pulverized product meets the following conditions: Dv50 is 0.3-15μm, Dv90 is 0.6-40μm, Dv99 is 0.65-60μm, Dv0 is 0.010-7μm, and Dv100 is 0.7-110μm.
[0013] The pulverized product is subjected to a second sintering treatment to obtain a modified lithium manganese iron phosphate cathode material.
[0014] The temperature of the first sintering treatment is 20–550℃, and the time is 2–10 h; the temperature of the second sintering treatment is 550–950℃, and the time is 4–22 h.
[0015] The modified lithium manganese iron phosphate cathode material includes a lithium manganese iron phosphate substrate, nickel doped in the lithium manganese iron phosphate substrate, and a carbon coating layer covering the surface of the lithium manganese iron phosphate substrate.
[0016] The positive electrode material as described above, wherein the manganese source includes at least one selected from manganese carbonate, manganese oxalate, manganese acetate, manganese nitrate, manganese chloride, and manganese sulfate; and / or,
[0017] The iron source includes at least one of ferrous oxalate, ferrous acetate, ferrous chloride, ferrous nitrate, and ferrous sulfate; and / or,
[0018] The nickel source includes at least one of nickel oxalate, nickel acetate, nickel chloride, nickel nitrate, and nickel sulfate; and / or,
[0019] The first slurry further includes a dopant, said dopant being a compound containing at least one element selected from Ti, V, Nb, Sb, Mg, and S; and / or,
[0020] The phosphorus source includes at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate; and / or,
[0021] The lithium source includes at least one of lithium carbonate, lithium hydroxide, and lithium acetate.
[0022] In the cathode material described above, the molar ratio of the manganese source to the iron source is (4-9):1; and / or,
[0023] The molar ratio of the nickel source to the iron source is (0.1–0.12):1; and / or,
[0024] The molar ratio of metal ions to phosphorus source in the first slurry is 1:1; and / or,
[0025] The molar ratio of the lithium source to the first precursor is (1.0–1.3):1; and / or,
[0026] The carbon source includes polyvinyl alcohol and glucose, and the mass ratio of polyvinyl alcohol to glucose is (1:1) to (5:3.5).
[0027] In a second aspect, the present invention provides a modified lithium manganese iron phosphate cathode material, which is prepared by the preparation method described in the first aspect.
[0028] In the cathode material described above, the compaction density of the modified lithium manganese iron phosphate cathode material is 2.4–2.65 g / cm³. 3 .
[0029] The cathode material described above, wherein the modified lithium manganese iron phosphate cathode material has a specific capacity of 145-165 mAh / g at a 0.2C rate.
[0030] The cathode material described above, wherein the modified lithium manganese iron phosphate cathode material has a specific capacity of 155-165 mAh / g at a 0.2C rate.
[0031] A third aspect of the present invention provides a positive electrode sheet comprising the modified lithium manganese iron phosphate positive electrode material described in the second aspect.
[0032] In a fourth aspect, the present invention provides a lithium-ion battery comprising the positive electrode sheet described in the third aspect.
[0033] The implementation of this invention has at least the following beneficial effects:
[0034] The method for preparing modified lithium manganese iron phosphate cathode material provided by this invention introduces a nickel source in the co-precipitation reaction to avoid excessive growth of some grains in the subsequent sintering process, thereby ensuring the high compaction density of the final product. Introducing a carbon source and adding a pulverization process between the two sintering processes can not only further control the particle size of the final product and facilitate the nano-sized grains, but also shorten the electron transport distance, thereby further improving the compaction density and conductivity. Applying this cathode material to batteries can improve the specific capacity and rate performance of the batteries. Attached Figure Description
[0035] Figure 1 This is a SEM image of the cathode material in Embodiment 1 of the present invention. Detailed Implementation
[0036] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0037] In a first aspect, the present invention provides a method for preparing a modified lithium manganese iron phosphate cathode material, comprising the following steps: mixing a manganese source, an iron source, a nickel source, a phosphorus source, and water to obtain a first slurry; treating the first slurry under a nitrogen atmosphere at a rotation speed of 200-300 r / min and a temperature of 50-60°C for 3-22 h to obtain a precipitated product; washing, filtering, and drying the precipitated product to obtain a first precursor; mixing the first precursor, a lithium source, polyvinyl alcohol, and glucose, and performing a first sintering treatment under an inert atmosphere to obtain a second precursor; wherein the mass of the carbon source is 4-10% of the sum of the masses of the first precursor and the lithium source; and pulverizing the second precursor to obtain a pulverized product. The particle size of the pulverized product is made to meet the following conditions: Dv50 is 0.3-15μm, Dv90 is 0.6-40μm, Dv99 is 0.65-60μm, Dv0 is 0.010-7μm, and Dv100 is 0.7-110μm. The pulverized product is then subjected to a second sintering treatment to obtain the modified lithium manganese iron phosphate cathode material. The temperature of the first sintering treatment is 20-500℃, and the time is 2-10h. The temperature of the second sintering treatment is 550-950℃, and the time is 4-22h. The modified lithium manganese iron phosphate cathode material includes a lithium manganese iron phosphate host, nickel doped in the lithium manganese iron phosphate host, and a carbon coating layer on the surface of the lithium manganese iron phosphate host.
[0038] The first slurry can be prepared by the following process: dissolving a manganese source and an iron source in deionized water, then adding a nickel source solution to obtain a first solution, wherein the total concentration of manganese and iron sources in the first solution is 0.5–5 mol / L; dissolving a phosphorus source in deionized water to obtain a second solution, wherein the concentration of phosphorus source in the second solution is 0.5–5 mol / L. The first and second solutions are then mixed to obtain the first slurry.
[0039] Specifically, the first solution is added to the second solution, and the mixture is treated under a nitrogen atmosphere at a rotation speed of 200–300 r / min and a temperature of 50–60°C for 3–22 h to obtain a precipitate. The temperature is 50–60°C, for example, 50°C, 55°C, 60°C, or any combination thereof, and the treatment time is 3–22 h, for example, 3 h, 5 h, 10 h, 15 h, 20 h, 22 h, or any combination thereof.
[0040] During the first slurry treatment at 200–300 rpm and 50–60°C for 3–22 hours under a nitrogen atmosphere, manganese, iron, nickel, and phosphorus sources undergo a co-precipitation reaction to obtain a precipitate. The precipitate contains at least a nickel-doped manganese ferric phosphate precursor, also known as the first precursor, and also contains a small amount of unreacted raw materials and water.
[0041] The precipitate is washed, filtered, and dried, which essentially removes unreacted raw materials and moisture. After washing, filtering, and drying, the first precursor is obtained.
[0042] The precipitated product is washed, filtered, and dried, directly evaporating the water to achieve rapid drying, which is faster than direct air drying or other drying methods. This is because manganese, iron, nickel, and phosphate ions, which have low diffusion coefficients, are easily unevenly dispersed in water, leading to uneven dispersion of the final dried product, which is detrimental to improving the performance of the cathode material. This invention achieves rapid drying by simultaneously stirring and drying, drying the manganese, iron, nickel, and phosphate ions into a solid state before they aggregate. This reduces the risk of uneven dispersion, resulting in a more uniform composition of the materials in the final first precursor, which is beneficial for obtaining modified lithium manganese iron phosphate cathode material with small particle size and narrow particle size distribution. The first precursor is a nickel-doped manganese iron phosphate precursor.
[0043] The first sintering process essentially involves the reaction of the first precursor with a lithium source and an organic carbon source to obtain the second precursor. During this process, the first precursor reacts with the lithium source to form a nickel-doped lithium manganese iron phosphate precursor, while a portion of the organic carbon source acts as a reducing agent to reduce the metal element, transforming the nickel-doped lithium manganese iron phosphate precursor into nickel-doped lithium manganese iron phosphate. Furthermore, the organic carbon source is in a fluid state, allowing it to uniformly coat the surface of both the nickel-doped lithium manganese iron phosphate and the nickel-doped lithium manganese iron phosphate precursor, resulting in the second precursor. This process is beneficial for obtaining modified lithium manganese iron phosphate cathode materials with small particle sizes and narrow particle size distributions, thereby improving uniformity.
[0044] The temperature of the first sintering treatment is 20 to 300°C, for example, 20°C, 40°C, 50°C, 100°C, 200°C, 300°C, 400°C, 500°C or any combination thereof, and the time is 2 to 10 hours, for example, 2 hours, 5 hours, 10 hours or any combination thereof.
[0045] The pulverization process can be assisted by a conventional high-energy grinding mill. The particle size of the pulverized product should meet the following conditions: Dv50 is 0.3–15 μm, Dv90 is 0.6–40 μm, and Dv100 is 1–75 μm. Alternatively, Dv99 can be 0.65–60 μm, and Dv0 can be 0.010–7 μm. Here, Dv50 refers to the particle size corresponding to a cumulative particle size volume distribution percentage of 50%, Dv90 refers to the particle size corresponding to a cumulative particle size volume distribution percentage of 90%, Dv99 refers to the particle size corresponding to a cumulative particle size volume distribution percentage of 99%, Dv0 refers to the minimum particle size, and Dv100 refers to the maximum particle size.
[0046] The second sintering process essentially promotes the formation of nickel-doped lithium manganese iron phosphate from the nickel-doped lithium manganese iron phosphate precursor, while simultaneously promoting the carbonization reaction of polyvinyl alcohol and glucose to form a carbon coating layer. At this point, the modified lithium manganese iron phosphate cathode material includes a lithium manganese iron phosphate substrate, nickel doped into the lithium manganese iron phosphate substrate, and a carbon layer coating the surface of the lithium manganese iron phosphate substrate.
[0047] The temperature of the second sintering treatment is 550 to 950°C, for example, 550°C, 600°C, 650°C, 700°C, 800°C, 900°C, 950°C or any combination thereof, and the time is 4 to 22 hours, for example, 4 hours, 10 hours, 20 hours, 22 hours or any combination thereof.
[0048] According to the research of this invention, applying the modified lithium manganese iron phosphate cathode material prepared by the above method to batteries is beneficial to improving the specific capacity and rate performance of the batteries. This is because, on the one hand, by introducing a nickel source in the co-precipitation reaction, the phenomenon of excessive growth of some grains in the subsequent sintering process is avoided, thereby helping to ensure the high compaction density of the final product. At the same time, the introduction of a carbon source helps to improve the conductivity of the cathode material. On the other hand, adding a pulverization process between the two sintering processes can not only further control the particle size and particle size distribution of the final product, but also shorten the electron transport distance, thereby helping to further improve the compaction density and conductivity. Applying this cathode material to batteries is beneficial to improving the specific capacity and rate performance of the batteries.
[0049] This invention does not limit the types of raw materials, and the specific types can be adjusted according to actual needs. For example, the manganese source includes at least one of manganese carbonate, manganese oxalate, manganese acetate, manganese nitrate, manganese chloride, and manganese sulfate; and / or, the iron source includes at least one of ferrous oxalate, ferrous acetate, ferrous chloride, ferrous nitrate, and ferrous sulfate; and / or, the nickel source includes at least one of nickel oxalate, nickel acetate, nickel chloride, nickel nitrate, and nickel sulfate; and / or, the first slurry also includes a dopant, which is a compound containing at least one of Ti, V, Nb, Sb, Mg, and S; and / or, the phosphorus source includes at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate; and / or, the lithium source includes at least one of lithium carbonate, lithium hydroxide, and lithium acetate.
[0050] This invention does not limit the amount of each raw material added, and can be adjusted according to actual needs. The molar ratio of manganese source to iron source is (4-9):1, for example, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or any two of them; and / or, the molar ratio of nickel source to iron source is (0.1-0.12):1, for example, 0.1:1, 0.11:1, 0.12:1 or any two of them; and / or, the molar ratio of metal ions to phosphorus source in the first slurry is 1:1; and / or, the molar ratio of lithium source to first precursor is (1.0-1.3):1, for example, 1.0:1, 1.1:1, 1.2:1, 1.3:1 or any two of them; and / or, the mass ratio of polyvinyl alcohol to glucose is (1:1) to (5:3.5).
[0051] Wherein, when the first paste only includes manganese source, iron source and nickel source, the molar amount of metal ions in the first paste is the total molar amount of manganese source, iron source and nickel source; when the first paste includes metal dopant in addition to manganese source, iron source and nickel source, the molar amount of metal ions in the first paste is the total molar amount of manganese source, iron source, nickel source and metal dopant.
[0052] Furthermore, the mass of the carbon source is 4.8% to 6.7% of the sum of the masses of the first precursor and the lithium source, for example, a range consisting of 4.8%, 5%, 5.5%, 6.0%, 6.7%, or any two of these.
[0053] In a second aspect, the present invention provides a modified lithium manganese iron phosphate cathode material, prepared using the method provided in the first aspect. Because it is prepared using the above method, the modified lithium manganese iron phosphate cathode material exhibits high compaction density and high conductivity. Applying this cathode material to batteries is beneficial for improving the specific capacity and rate performance of the batteries.
[0054] In some embodiments, the compaction density of the modified lithium manganese iron phosphate cathode material is 2.4–2.65 g / cm³. 3 For example, 2.4 g / cm 3 2.50g / cm 3 2.55g / cm 3 2.60g / cm 3 2.65g / cm 3 or a range consisting of any two of them.
[0055] In some embodiments, the modified lithium manganese iron phosphate cathode material has a specific capacity of 145–165 mAh / g at 0.2C rate, a 0.5C / 0.1C constant current charge ratio of 87–97%, and a 3C / 0.5C constant current discharge ratio of [missing information].
[0056] 92-99%; furthermore, the modified lithium manganese iron phosphate cathode material has a specific capacity of 155-165 mAh / g at 0.2C rate, a constant current charging ratio of 92-96% at 0.5C / 0.1C, and a constant current discharging ratio of 96-99% at 3C / 0.5C.
[0057] A third aspect of the present invention provides a positive electrode sheet comprising the modified lithium manganese iron phosphate positive electrode material provided in the second aspect.
[0058] The positive electrode sheet of the present invention can also be prepared using conventional techniques in the art. Specifically, the above-mentioned positive electrode material, conductive agent, and binder can be uniformly dispersed in a solvent to obtain a positive electrode active layer slurry. Then, the positive electrode active layer slurry is coated on at least one functional surface of the positive electrode current collector, and after drying, the positive electrode sheet of the present invention can be obtained.
[0059] A fourth aspect of the present invention provides a lithium-ion battery, the lithium-ion battery comprising the positive electrode provided in the third aspect.
[0060] The lithium-ion battery of the present invention includes, in addition to the positive electrode, a separator, a negative electrode, and an electrolyte. The composition of the negative electrode can refer to conventional negative electrode sheets in the art, and the separator can also be a conventionally used separator in the art, such as PP film or PE film. The lithium-ion battery of the present invention can be prepared using conventional methods in the art. Specifically, the positive electrode, separator, and negative electrode can be sequentially stacked, and a cell can be obtained through a stacking or winding process. Then, the lithium-ion battery is obtained through baking, electrolyte injection, formation, and packaging processes.
[0061] The present invention will be further described below through specific embodiments and comparative examples.
[0062] Example 1
[0063] (1) Dissolve manganese oxalate and ferrous oxalate in deionized water at a molar ratio of 5:1 to prepare a mixed solution A of manganese oxalate and ferrous oxalate (total concentration of manganese oxalate and ferrous oxalate is 0.5 mol / L); dissolve ammonium dihydrogen phosphate in deionized water to prepare a 0.5 mol / L phosphorus source solution B (also known as the second solution); dissolve nickel oxalate in deionized water to prepare a 0.01 mol / L nickel source solution C;
[0064] (2) Mix solution C and solution A evenly to obtain the first solution; add the first solution to the second solution, stir at 200 r / min under nitrogen protection, and heat at 55℃ for 21 h to obtain the precipitate; wherein the molar ratio of metal ions in the first solution to phosphorus source in the second solution is 1:1;
[0065] The precipitate was washed, filtered, and dried to obtain the first precursor.
[0066] (3) The first precursor, lithium carbonate, glucose and polyvinyl alcohol are mixed and heated to 280°C in a nitrogen atmosphere and calcined at 280°C for 8 hours. Then the mixture is cooled to room temperature to obtain the second precursor. The molar ratio of lithium carbonate to the first precursor is 1:1, the mass of glucose is 3wt% of the total mass of the first precursor and lithium carbonate, and the mass of polyvinyl alcohol is 2wt% of the total mass of the first precursor and lithium carbonate.
[0067] (4) The second precursor is pulverized to obtain the pulverized product; the particle size of the pulverized product meets the following conditions: Dv50=1.12μm, Dv0=0.13μm, Dv90=10.56μm, Dv99=15.18μm, Dv100=25.26μm;
[0068] (5) The pulverized product was heated to 670℃ in a nitrogen atmosphere and calcined at 670℃ for 20 hours. After cooling to room temperature, the modified lithium manganese iron phosphate cathode material was obtained. The scanning electron microscope image is shown below. Figure 1 As shown.
[0069] Example 2
[0070] (1) Dissolve manganese oxalate and ferrous oxalate in deionized water at a molar ratio of 5:1 to prepare a mixed solution A of manganese oxalate and ferrous oxalate (concentration of manganese oxalate and ferrous oxalate is 0.5 mol / L); dissolve ammonium dihydrogen phosphate in deionized water to prepare a 0.5 mol / L phosphorus source solution B (also known as the second solution); dissolve nickel oxalate in deionized water to prepare a 0.01 mol / L nickel source solution C;
[0071] (2) Mix solution C and solution A evenly to obtain the first solution; add the first solution to the second solution, stir at 300 r / min under nitrogen protection, and heat at 60℃ for 10 h to obtain the precipitate; wherein the molar ratio of metal ions in the first solution to phosphorus source in the second solution is 1:1;
[0072] After washing, filtering and drying the first slurry, the first precursor is obtained;
[0073] (3) The first precursor, lithium carbonate, polyvinyl alcohol and glucose are mixed and heated to 250°C in a nitrogen atmosphere and calcined at 250°C for 10 hours. Then the mixture is cooled to room temperature to obtain the second precursor. The molar ratio of lithium carbonate to the first precursor is 1:1, glucose is 3 wt% of the total mass of the first precursor and lithium carbonate, and polyvinyl alcohol is 1.8 wt% of the total mass of the first precursor and lithium carbonate.
[0074] (4) The second precursor is pulverized to obtain the pulverized product; the particle size of the pulverized product meets the following conditions: Dv50=1.25μm, Dv0=0.15μm, Dv90=12.11μm, Dv99=16.12μm, Dv100=27.32μm;
[0075] The pulverized product was heated to 800°C in a nitrogen atmosphere and calcined at 800°C for 20 hours. After cooling to room temperature, the modified lithium manganese iron phosphate cathode material was obtained.
[0076] Example 3
[0077] (1) Dissolve manganese oxalate and ferrous oxalate in deionized water at a molar ratio of 5:1 to prepare a mixed solution A of manganese oxalate and ferrous oxalate (concentration of manganese oxalate and ferrous oxalate is 0.5 mol / L); dissolve ammonium dihydrogen phosphate in deionized water to prepare a 0.5 mol / L phosphorus source solution B (also known as the second solution); dissolve nickel oxalate in deionized water to prepare a 0.01 mol / L nickel source solution C;
[0078] (2) Mix solution C and solution A evenly to obtain the first solution; add the first solution to the second solution, stir at 250 r / min under nitrogen protection, and heat at 58℃ for 15 h to obtain the precipitate; wherein the molar ratio of metal ions in the first solution to phosphorus source in the second solution is 1:1;
[0079] The precipitate was washed, filtered, and dried to obtain the first precursor.
[0080] (3) The first precursor, lithium carbonate, glucose and polyvinyl alcohol are mixed and heated to 280°C in a nitrogen atmosphere and calcined at 280°C for 8 hours. Then the mixture is cooled to room temperature to obtain the second precursor. The molar ratio of lithium carbonate to the first precursor is 1:1, glucose is 3wt% of the total mass of the first precursor and lithium carbonate, and polyvinyl alcohol is 3.7wt% of the total mass of the first precursor and lithium carbonate.
[0081] (4) The second precursor is pulverized to obtain the pulverized product; the particle size of the pulverized product meets the following conditions: Dv50=1.23μm, Dv0=0.15μm, Dv90=12.15μm, Dv99=16.17μm, Dv100=27.39μm;
[0082] The pulverized product was heated to 670°C in a nitrogen atmosphere and calcined at 670°C for 20 hours. After cooling to room temperature, the modified lithium manganese iron phosphate cathode material was obtained.
[0083] Example 4
[0084] (1) Dissolve manganese acetate and ferrous chloride in deionized water at a molar ratio of 5:1 to prepare a mixed solution A of manganese acetate and ferrous chloride (total concentration of manganese acetate and ferrous chloride is 0.5 mol / L); dissolve diammonium hydrogen phosphate in deionized water to prepare a 0.5 mol / L phosphorus source solution B (also known as the second solution); dissolve nickel oxalate in deionized water to prepare a 0.01 mol / L nickel source solution C;
[0085] (2) Mix solution C and solution A evenly to obtain the first solution; add the first solution to the second solution, stir at 300 r / min under nitrogen protection, and heat at 55℃ for 21 h to obtain the precipitate; wherein the molar ratio of metal ions in the first solution to phosphorus source in the second solution is 1:1;
[0086] The precipitate was washed, filtered, and dried to obtain the first precursor.
[0087] (3) The first precursor, lithium acetate, polyvinyl alcohol and glucose are mixed and heated to 280°C in a nitrogen atmosphere and calcined at 280°C for 8 hours. Then the mixture is cooled to room temperature to obtain the second precursor. The molar ratio of lithium acetate to the first precursor is 2:1, glucose is 3wt% of the total mass of the first precursor and lithium acetate, and polyvinyl alcohol is 2wt% of the total mass of the first precursor and lithium acetate.
[0088] (4) The second precursor is pulverized to obtain the pulverized product; the particle size of the pulverized product meets the following conditions: Dv50=1.21μm, Dv0=0.11μm, Dv90=12.13μm, Dv99=16.25μm, Dv100=27.45μm;
[0089] The pulverized product was heated to 670°C in a nitrogen atmosphere and calcined at 670°C for 20 hours. After cooling to room temperature, the modified lithium manganese iron phosphate cathode material was obtained.
[0090] Example 5
[0091] (1) Dissolve manganese nitrate and ferrous sulfate in deionized water at a molar ratio of 5:1 to prepare a mixed solution A of manganese nitrate and ferrous sulfate (the concentration of manganese nitrate and ferrous sulfate is 0.5 mol / L); dissolve ammonium phosphate in deionized water to prepare a 0.5 mol / L phosphorus source solution B (also known as the second solution); dissolve nickel oxalate in deionized water to prepare a 0.01 mol / L nickel source solution C;
[0092] (2) Mix solution C and solution A evenly to obtain the first solution; add the first solution to the second solution, stir under nitrogen protection, and heat at 55°C for 21 hours to obtain the first slurry; wherein the molar ratio of metal ions in the first solution to phosphorus source in the second solution is 1:1;
[0093] After washing, filtering and drying the first slurry, the first precursor is obtained.
[0094] (3) The first precursor, lithium acetate, glucose and polyvinyl alcohol are mixed and heated to 280°C in a nitrogen atmosphere and calcined at 280°C for 8 hours. Then the mixture is cooled to room temperature to obtain the second precursor. The molar ratio of lithium acetate to the first precursor is 2:1, glucose is 3wt% of the total mass of the first precursor and lithium acetate, and polyvinyl alcohol is 2wt% of the total mass of the first precursor and lithium acetate.
[0095] (4) The second precursor is pulverized to obtain the pulverized product; the particle size of the pulverized product meets the following conditions: Dv50=1.22μm, Dv0=0.15μm, Dv90=12.15μm, Dv99=16.25μm, Dv100=27.81μm;
[0096] The pulverized product was heated to 670°C in a nitrogen atmosphere and calcined at 670°C for 20 hours. After cooling to room temperature, the modified lithium manganese iron phosphate cathode material was obtained.
[0097] Example 6
[0098] The preparation process is basically the same as in Example 1, except that only glucose is introduced and polyvinyl alcohol is not introduced. The specific preparation process is as follows:
[0099] (1) Dissolve manganese oxalate and ferrous oxalate in deionized water at a molar ratio of 5:1 to prepare a mixed solution A of manganese oxalate and ferrous oxalate (concentration of manganese oxalate and ferrous oxalate is 0.5 mol / L); dissolve ammonium dihydrogen phosphate in deionized water to prepare a 0.5 mol / L phosphorus source solution B (also known as the second solution); dissolve nickel oxalate in deionized water to prepare a 0.01 mol / L nickel source solution C;
[0100] (2) Mix solution C and solution A evenly to obtain the first solution; add the first solution to the second solution, stir under nitrogen protection, and heat at 55°C for 21 hours to obtain the first slurry; wherein the molar ratio of metal ions in the first solution to phosphorus source in the second solution is 1:1;
[0101] After washing, filtering and drying the first slurry, the first precursor is obtained.
[0102] (3) The first precursor, lithium carbonate and glucose are mixed and heated to 280°C in a nitrogen atmosphere and calcined at 280°C for 8 hours. Then the mixture is cooled to room temperature to obtain the second precursor. The molar ratio of lithium carbonate to the first precursor is 1:1 and the glucose is 5 wt% of the total mass of the first precursor and lithium carbonate.
[0103] (4) The second precursor is pulverized to obtain the pulverized product; the particle size of the pulverized product meets the following conditions: Dv50=1.25μm, Dv0=0.15μm, Dv90=12.31μm, Dv99=16.21μm, Dv100=27.33μm;
[0104] (5) The pulverized product was heated to 670°C in a nitrogen atmosphere and calcined at 670°C for 20 hours. After cooling to room temperature, the modified lithium manganese iron phosphate cathode material was obtained.
[0105] Example 7
[0106] The preparation process is basically the same as in the examples, except that a titanium source is added, specifically including the following steps:
[0107] (1) Dissolve manganese oxalate and ferrous oxalate in deionized water at a molar ratio of 5:1 to prepare a mixed solution A of manganese oxalate and ferrous oxalate (total concentration of manganese oxalate and ferrous oxalate is 0.5 mol / L); dissolve ammonium dihydrogen phosphate in deionized water to prepare a 0.5 mol / L phosphorus source solution B (also known as the second solution); dissolve 0.01 mol / L nickel oxalate and 0.01 mol / L titanium oxalate in deionized water to prepare solution C;
[0108] (2) Mix solution C and solution A evenly to obtain the first solution; add the first solution to the second solution, stir at 200 r / min under nitrogen protection, and heat at 55℃ for 21 h to obtain the precipitate; wherein the molar ratio of metal ions in the first solution to phosphorus source in the second solution is 1:1;
[0109] The precipitate was washed, filtered, and dried to obtain the first precursor.
[0110] (3) The first precursor, lithium carbonate, glucose and polyvinyl alcohol are mixed and heated to 280°C in a nitrogen atmosphere and calcined at 280°C for 8 hours. Then the mixture is cooled to room temperature to obtain the second precursor. The molar ratio of lithium carbonate to the first precursor is 1:1, the mass of glucose is 3wt% of the total mass of the first precursor and lithium carbonate, and the mass of polyvinyl alcohol is 2wt% of the total mass of the first precursor and lithium carbonate.
[0111] (4) The second precursor is pulverized to obtain the pulverized product; the particle size of the pulverized product meets the following conditions: Dv50=1.23μm, Dv0=0.12μm, Dv90=12.33μm, Dv99=16.24μm, Dv100=27.37μm;
[0112] The pulverized product was heated to 670°C in a nitrogen atmosphere and calcined at 670°C for 20 hours. After cooling to room temperature, the positive electrode material of this embodiment was obtained.
[0113] Example 8
[0114] The preparation process is basically the same as in Example 1, except that a vanadium source is added, specifically including the following steps:
[0115] (1) Dissolve manganese oxalate and ferrous oxalate in deionized water at a molar ratio of 5:1 to prepare a mixed solution A (0.5 mol / L concentration of manganese oxalate and ferrous oxalate); dissolve ammonium dihydrogen phosphate in deionized water to prepare a 0.5 mol / L phosphorus source solution B (also known as the second solution); dissolve 0.01 mol / L nickel oxalate and 0.01 mol / L vanadium oxalate in deionized water to prepare solution C.
[0116] (2) Mix solution C and solution A evenly to obtain the first solution; add the first solution to the second solution, stir at 200 r / min under nitrogen protection, and heat at 55℃ for 21 h to obtain the precipitate; wherein the molar ratio of metal ions in the first solution to phosphorus source in the second solution is 1:1;
[0117] The precipitate was washed, filtered, and dried to obtain the first precursor.
[0118] (3) The first precursor, lithium carbonate, glucose and polyvinyl alcohol are mixed and heated to 280°C in a nitrogen atmosphere and calcined at 280°C for 8 hours. Then the mixture is cooled to room temperature to obtain the second precursor. The molar ratio of lithium carbonate to the first precursor is 1:1, the mass of glucose is 3wt% of the total mass of the first precursor and lithium carbonate, and the mass of polyvinyl alcohol is 2wt% of the total mass of the first precursor and lithium carbonate.
[0119] (4) The second precursor is pulverized to obtain the pulverized product; the particle size of the pulverized product meets the following conditions: Dv50=1.28μm, Dv0=0.16μm, Dv90=12.63μm, Dv99=16.44μm, Dv100=27.57μm;
[0120] The pulverized product was heated to 670°C in a nitrogen atmosphere and calcined at 670°C for 20 hours. After cooling to room temperature, the positive electrode material of this embodiment was obtained.
[0121] Comparative Example 1
[0122] The preparation process is basically the same as in Example 1, except that nickel oxalate is not introduced. The specific preparation process is as follows:
[0123] (1) Dissolve manganese oxalate and ferrous oxalate in deionized water at a molar ratio of 5:1 to prepare a mixed solution A of manganese oxalate and ferrous oxalate (total concentration of manganese oxalate and ferrous oxalate is 0.5 mol / L); dissolve ammonium dihydrogen phosphate in deionized water to prepare a 0.5 mol / L phosphorus source solution B.
[0124] (2) Mix solution A and solution B, stir under nitrogen protection, heat at 55°C for 21 h, wash and dry to obtain manganese iron phosphate precursor; wherein the molar ratio of metal ions in solution A to phosphorus source in solution B is 1:1;
[0125] (3) Mix manganese iron phosphate precursor, lithium carbonate, glucose and polyvinyl alcohol, heat to 280°C in a nitrogen atmosphere, and calcine at 280°C for 8 hours. Then cool to room temperature to obtain the second precursor. The molar ratio of lithium carbonate to the first precursor is 1:1. Glucose is 3wt% of the total mass of manganese iron phosphate precursor and lithium carbonate, and polyvinyl alcohol is 2wt% of the total mass of manganese iron phosphate precursor and lithium carbonate.
[0126] (4) The second precursor is pulverized to obtain the pulverized product; the particle size of the pulverized product meets the following conditions: Dv50=1.23μm, Dv0=0.13μm, Dv90=12.01μm, Dv99=16.02μm, Dv100=27.12μm;
[0127] (5) The pulverized product was heated to 670°C in a nitrogen atmosphere and calcined at 670°C for 20 hours. After cooling to room temperature, the modified lithium manganese iron phosphate cathode material was obtained.
[0128] Comparative Example 2
[0129] This comparative example uses a high-temperature solid-state method to prepare lithium manganese iron phosphate cathode materials.
[0130] 1.1 mol of lithium hydroxide, 1 mol of phosphoric acid, 0.5 mol of ferrous oxalate, 0.5 mol of manganese oxalate, and 0.04 mol of nickel oxalate were dissolved in 230 mL of water and stirred until homogeneous. Then, 14.04 g of glucose was added as a carbon source, along with 1–2 drops of modified acrylate dispersant and 800 g of 0.5–10 μm zirconium balls. The slurry was ground at 2000 rpm for 2.5 h until the solid particle size Dv50 = 0.908 μm, yielding a slurry. The slurry was then fed into a spray dryer for drying to obtain the first precursor powder.
[0131] The first precursor powder was subjected to a first heat treatment under nitrogen protection, and after cooling, the second precursor particles were obtained. The second precursor particles were composed of carbon-coated lithium manganese iron phosphate particles. The conditions for the first heat treatment were: temperature 600℃ and time 8h.
[0132] 50g of second precursor particles, 2.57g of polyvinyl alcohol, and 2g of glucose were added sequentially to 200g of deionized water, stirred and dispersed, and then processed using a ball mill with a total energy input of 600Wh to obtain the second precursor slurry. The slurry was then introduced into a spray dryer for drying (drying conditions: temperature 300℃, time 5s) to obtain the third precursor particles.
[0133] The modified lithium manganese iron phosphate cathode material of this comparative example was obtained by heating the third precursor particles under nitrogen protection (temperature 650℃, time 8h) and then cooling them down.
[0134] Comparative Example 3
[0135] The preparation process is basically the same as that in Example 1, except that: in step (3), the mass of glucose is 0.1% of the total mass of the first precursor and lithium carbonate, the mass of polyvinyl alcohol is 0.2wt% of the total mass of the first precursor and lithium carbonate, and other conditions remain unchanged, thus obtaining the cathode material of this comparative example.
[0136] Comparative Example 4
[0137] The preparation process is basically the same as that in Example 1, except that in step (3), the mass of glucose is 3wt% of the total mass of the first precursor and lithium carbonate, and the mass of polyvinyl alcohol is 10wt% of the total mass of the first precursor and lithium carbonate. Other conditions remain unchanged, and the positive electrode material of this comparative example is obtained.
[0138] Test case
[0139] 1. Compacted density test
[0140] The positive electrode material is dried to obtain dried material. This dried material is then filled into a cylindrical mold, and pressure is applied to 30 MPa using a press and maintained for 2 minutes. At this time, the mass m0 of the dried material, the height L inside the cylindrical mold, and the diameter D1 inside the mold are measured. According to ρ = 4m0 / πD1... 2 L is used to calculate the compaction density ρ.
[0141] 2. Conductivity test
[0142] The positive electrode material powder was filled into the entire mold. A pressure of 3 tons was applied to the tablet press, and after holding the pressure for 1 minute, the resistance R was measured. According to σ=4(L2-L1) / πD2 2 R is used to calculate the electrical conductivity σ of the powder, in Ω·m; in the formula, L1 represents the height of the mold before compaction; L2 represents the height of the mold after compaction; D represents the diameter of the mold; R represents the resistance, in Ω.
[0143] 3. Cyclic performance test
[0144] A positive electrode slurry was prepared by mixing positive electrode material, conductive carbon black (SP), polyvinylidene fluoride (PVDF) in a mass ratio of 80:15:5 with anhydrous ethanol and stirring until homogeneous. This slurry was then coated onto aluminum foil (9 μm thick) at a coating density of 1.6 mg / cm³. 2 After drying and rolling, a positive electrode sheet (24 μm thick and 12 mm in diameter) was obtained; the conductive carbon black was purchased from Tianjin Yiborui Chemical Co., Ltd. as SP conductive agent; the CAS number of polyvinylidene fluoride is 24937-79-9.
[0145] Battery assembly: In an argon-filled glove box, button-type half-cells of specification CR2032 are installed. The positive electrode, separator, and negative electrode are stacked in sequence to obtain the cell. The aluminum-plastic film is punched using a punching die, and then the cell is sealed with the punched aluminum-plastic film. The cell is baked until the moisture content is within acceptable limits, and then the electrolyte is injected. After formation and secondary sealing, the button cell is obtained.
[0146] The electrolyte consists of a lithium metal sheet (1 mm thick and 12 mm in diameter), a Celgard2500 diaphragm (14 mm in diameter and 25 μm thick) from KELOD, and a 1 mol / L lithium hexafluorophosphate (LiPF6) electrolyte. The electrolyte solvent is ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1.
[0147] Cycle performance test: The battery test system (LAND CT2001A) was used for testing. The test voltage was 2.5 to 4.5V and the test temperature was 25℃. The first discharge specific capacity was tested under the condition of 0.2C.
[0148] The test results are shown in Table 1.
[0149] Table 1
[0150]
[0151] As shown in Table 1, the modified lithium manganese iron phosphate cathode material prepared by the preparation method provided by the present invention has excellent compaction density, resistivity and capacity.
[0152] The preferred embodiments and experimental verifications of the present invention have been described in detail above. It should be understood that those skilled in the art can make numerous modifications and variations based on the concept of the present invention without creative effort. Therefore, all technical solutions that can be obtained by those skilled in the art based on the concept of the present invention through logical analysis, reasoning, or limited experimentation on the basis of existing technology should be within the scope of protection defined by the claims.
Claims
1. A method for preparing a modified lithium manganese iron phosphate cathode material, characterized in that, Includes the following steps: Manganese, iron, nickel, and phosphorus sources are mixed with water to obtain the first slurry; The first slurry was treated under a nitrogen atmosphere at a rotation speed of 200-300 r / min and a temperature of 50-60°C for 10-22 h to obtain a precipitated product. The precipitate was washed, filtered, and dried to obtain the first precursor. The first precursor, lithium source, and carbon source are mixed and subjected to a first sintering treatment under an inert atmosphere to obtain a second precursor; the mass of the carbon source is 4 to 10% of the sum of the mass of the first precursor and the lithium source. The second precursor is pulverized to obtain a pulverized product, and the particle size of the pulverized product meets the following conditions: Dv50 is 0.3~15μm, Dv90 is 0.6~40μm, Dv99 is 0.65~60μm, Dv0 is 0.010~7μm, and Dv100 is 0.7~110μm. The pulverized product is subjected to a second sintering treatment to obtain a modified lithium manganese iron phosphate cathode material. The temperature of the first sintering treatment is 20~550℃ and the time is 2~10h; the temperature of the second sintering treatment is 550~950℃ and the time is 4~22h. The modified lithium manganese iron phosphate cathode material includes a lithium manganese iron phosphate substrate, nickel doped in the lithium manganese iron phosphate substrate, and a carbon coating layer covering the surface of the lithium manganese iron phosphate substrate. The first slurry is prepared by the following process: dissolving a manganese source and an iron source in deionized water, adding a nickel source solution to obtain a first solution, wherein the total concentration of the manganese source and the iron source in the first solution is 0.5~5 mol / L; dissolving a phosphorus source in the deionized water to obtain a second solution, wherein the concentration of the phosphorus source in the second solution is 0.5~5 mol / L; and mixing the first solution and the second solution to obtain the first slurry.
2. The preparation method according to claim 1, characterized in that, The manganese source includes at least one of manganese carbonate, manganese oxalate, manganese acetate, manganese nitrate, manganese chloride, and manganese sulfate; and / or, The iron source includes at least one of ferrous oxalate, ferrous acetate, ferrous chloride, ferrous nitrate, and ferrous sulfate; and / or, The nickel source includes at least one of nickel oxalate, nickel acetate, nickel chloride, nickel nitrate, and nickel sulfate; and / or, The first slurry further includes a dopant, said dopant being a compound containing at least one element selected from Ti, V, Nb, Sb, Mg, and S; and / or, The phosphorus source includes at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate; and / or, The lithium source includes at least one of lithium carbonate, lithium hydroxide, and lithium acetate.
3. The preparation method according to claim 1 or 2, characterized in that, The molar ratio of the manganese source to the iron source is (4~9):1; and / or, The molar ratio of the nickel source to the iron source is (0.1~0.12):1; and / or, The molar ratio of metal ions to phosphorus source in the first slurry is 1:1; and / or, The molar ratio of the lithium source to the first precursor is (1.0~1.3):1; and / or, The carbon source includes polyvinyl alcohol and glucose, and the mass ratio of polyvinyl alcohol to glucose is (1:1) to (5:3.5).
4. The preparation method according to claim 1, characterized in that, The mass of the carbon source is 4.8 to 6.7% of the sum of the masses of the first precursor and the lithium source.
5. A modified lithium iron phosphate cathode material, characterized in that, It is prepared by the preparation method according to any one of claims 1-4.
6. The positive electrode material according to claim 5, characterized in that, The compaction density of the modified lithium manganese iron phosphate cathode material is 2.4~2.65 g / cm³. 3 .
7. The cathode material according to claim 5, characterized in that, The modified lithium manganese iron phosphate cathode material has a specific capacity of 145~165 mAh / g at a 0.2C rate.
8. The positive electrode material according to claim 5, characterized in that, The modified lithium manganese iron phosphate cathode material has a specific capacity of 155~165 mAh / g at a 0.2C rate.
9. A positive electrode plate, characterized in that, The positive electrode comprises the modified lithium manganese iron phosphate positive electrode material as described in any one of claims 5-8.
10. A lithium-ion battery, characterized in that, The lithium-ion battery includes the positive electrode sheet as described in claim 9.
Citation Information
Patent Citations
Nickel-doped lithium iron manganese phosphate positive electrode material as well as preparation method and application thereof
CN114566646A